2023
DOI: 10.3390/su15021065
|View full text |Cite
|
Sign up to set email alerts
|

Research on Design Strategy of Mask Recycling Service Based on Behavior Environment

Abstract: The global novel coronavirus pandemic has caused a surge in the use of masks worldwide. A large number of used masks that have not been properly handled enter the environment, which caused and will cause serious ecological problems. The purpose of this study is to propose a solution to the problem of mask management from the perspective of science of design, and to build a good mask recycling service design strategy through the combination of design and psychology. Firstly, based on the theory of behavioral en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…This showed that the position of masks changed, originally from disposable medical appliances to the commonly used items in life. 12 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This showed that the position of masks changed, originally from disposable medical appliances to the commonly used items in life. 12 …”
Section: Resultsmentioning
confidence: 99%
“…This showed that the position of masks changed, originally from disposable medical appliances to the commonly used items in life. 12 The extensive usage of masks, sanitizers, and synthetic-based personal protective equipment (PPE) kits by healthcare professionals and the overall community has resulted in massive amounts of plastic trash, with no effective measures or policies in place to reduce its severity. It is commonplace to wear face masks as a way of protecting oneself against Covid-19.…”
Section: The Reality Of Facemask Waste During the Covid-19 Pandemicmentioning
confidence: 99%